OPTIMALISASI KEBUTUHAN GIZI PADA MENU MAKANAN IBU HAMIL ANEMIA MENGGUNAKAN METODE BRACH AND BOUND (Studi Kasus di Kecamatan Ampana Tete Kabupaten Tojo Una-Una Provinsi Sulawesi Tengah) - Zulhajrah, Zulhajrah; Jaya, A I; Sahari, A (Program Studi Matematika, Universitas Tadulako, 2018)
Anemia in pregnancy is a common problem because it reflects the value of socio-economic welfare of society and has had enormous influence on the quality of human resources. Settings menu maternal anemia is an effort to maintain the condition of pregnant women with anemia. This study aims to obtain optimal value nutritional needs of pregnant women anemia in Ampana Tete District of Tojo Una-Una Central Sulawesi province by using the branch and bound method. The parameters used in this study are the type of staple foods (ð‘¥1 ), the type of vegetable(ð‘¥2 ), types of fruit(ð‘¥3 ), types of side dishes(ð‘¥4 ), green beans(ð‘¥5 ), and milk(ð‘¥6 ), Results show 1st, 2 nd, and 3 rd of 36 combinations known to the most optimal combination for all trimester is a combination of 14. For the first trimester are as many as rice, 348 g spinach were 116 g,chicken eggs as 482 gmuch,and green beans 138 g, at a cost of ð‘…ð‘. 15680,00, 2nd trimester is as much as rice, 381 g spinach amount to 167 g, chicken 690 g eggs, and green beans as much as 154 g and of milk 3 g at a cost of ð‘…ð‘ 20498,50, and the third trimester is rice, 345 g spinach, 127 g, chicken 914 g eggs, and green beans 176 g, at a cost of ð‘…ð‘. 24086.00 per day. The analysis has not been as expected because one of the drawbacks is the use of linear programming linearity as sumption that sometimes does not correspond to reality.